Angiosperms tree species: use of identification keys based on vegetative features in an Android application and a website - Santos, Fernando Santiago dos; Sant’Ana, Gabriela Zominhani (Revista Hipótese, 2016)
The present report presents information of an identification key based on vegetative characteristics of tree species found within the Federal Institute of Science and Technology of São Paulo, São Roque Campus for smart-phones and a web site. The specific survey was based upon a previous study at the institution, from which a check-list of tree species was found. To develop the identification key, a survey of the vegetative specific characters was employed, thus preparing the on-line key and the Android® application for smart-phones. The total number of species is 80, belonging to 36 families, three belonging to the group of gymnosperms and 33 to the group of Flowering Plants.
Keywords: Android® Application; Smart-phones; Check-list; Gymnosperms